FORMATION OF NON-STATE PENSION FUND IN THE PENSION SYSTEM IN RUSSIAN FEDERATION - L. Kruglyak; G. Fatkhlislamova (Вестник университета)
The main purpose of the article is to create a denition of the genesis of such a large institutional investor as non-state pension funds (NPFs) and their current status in the pension system of the Russian Federation. The article provides a detailed study of the emergence of APFs in the market economy of Russia, as well as a study of the main parameters of the institutional and functional structure of relations on the forma-tion of NPFs of pension savings and pension reserves. The modern tendencies of APF de-velopment in the pension system of Russia are revealed.